The original formula for predicting the survival of gastric cancer patients undergoing surgical treatment - Sira, O. V.; Kirkilevsky, S. I.; Tkachenko, O. I.; Dubinina, V. G.; Mashukov, A. A.; Bilenko, A. A.; Merlich, S. V.; Maksimovsky, V. E.; Zgura, A. N.; Ratsiborsky, D. V.; Shilin, I. V.; Boychenko, A. I. (RS Global Sp. z O. O., 2018)
The purpose of this work was to find ways to predict the survival of gastric cancer patients. The study included 221 patients who were radically operated in the abdominal department of the Odessa Regional Oncology Center from 2007 to 2013. The life expectancy of this group of patients was measured in months. From the factors given in the article, only the age of the patient, the presence and invasion in neighboring organs and the number of organs resected during the operation were those factors that had a significant impact on the prognosis. A formula was obtained for the formal evaluation of the duration of patients. The results are preliminary. Conclusions. As a result of the regression analysis, a polynomial (formula) was obtained, which can be used to predict the survival of patients who underwent surgery for gastric cancer. There is a need to create clearer gradations of survival dependencies of cancer patients from different clinical and morphological situations. A mathematical apparatus with many variables can be used to create similar models for the analysis of survival in other types of pathology.
Keywords: stomach cancer; mathematical formula; immunohistochemistry; survival